Bulgarian Projects in the Field of the Digital Transformation of Education and Their Role in Building Digital Literacy in the Children in Primary School - Parijkova, Lubomira; Simeonov, Kristiyan (Bobcatsss, 2023)
In the recent decades the digital transformation has been radically changing every aspect of our social life on both global and national level. Following the development of the new ICT technologies, there has been a growing need for rapid adaptation to the new professional, educational and recreational possibilities. In 2020 was developed a strategic document outlining the national guidelines for the digital transformation of Bulgaria for the 2020-2030 period. It contains the essential principles of digital transformation and aims to facilitate the development of innovative models in a number of areas, such as scientific research, digital education etc. The contemporary education requires the development and implementation of flexible platforms and appropriate electronic content suitable for all age groups. This calls for modern ICT equipment and software as well as trained educators that can provide appropriate digital education and relevant learning content. The article examines the Bulgarian projects for digital transformation in education and their key role in ensuring the learning process (improving the learning conditions) for primary school children in the current situation of a global pandemic as well as their prospects in the context of the evolving modern information environment. The good practices and projects in Bulgarian education and the challenges they are facing in the implementation of a successful digital transformation are described.